A tannic acid-based intumescent flame retardant for improving flame retardancy of epoxy composites - Xiaosui Chen; Yaoting Ma; Shuzheng Liu; Aiqing Zhang; Wei Liu; Shengchao Huang (Advanced Industrial and Engineering Polymer Research)
A biomass intumescent flame retardant (TA-g-DOPO) was fabricated from tannic acid (TA) and 9, 10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide (DOPO) through the bridge of silane coupling agent (KH560), which showed a low degradation rate at Tmax of 2.71%/min and a high char yield of 55.8%. Then, various EP composites with 4–10% TA-g-DOPO were prepared. Due to the presence of flexible silane structures and rigid phosphaphenanthrene rings as well as the remained phenol groups (tending to form hydrogen bonds with epoxy matrix), EP composite with a high content of 10% TA-g-DOPO exhibited no deterioration on the tensile and impact properties as well as the glass transition temperature (Tg) when compared with pure EP. More importantly, it reached a high LOI value of 30.3% and passed a V-0 rating in the UL-94 burning test. Additionally, its peak heat release rate (PHRR), total heat release (THR) and average mass loss rate (av-MLR) decreased by 23.2%, 15.5% and 30.2% respectively. Analyses from the condensed char and pyrolysis gases indicated that the improved flame retardancy was mainly attributed to the cooperation of the free-radical quenching effect of P-containing radicals and phenoxy radicals working in stages (derived from DOPO and TA respectively) and the physical barrier effect caused by the highly graphited, intumescent and porous char layer (reinforced by P- and Si-containing cross-linked structures). This work provides a sustainable biomass flame retardant with good flame-retarding efficiency based on TA.